ABU NUWAS (Intelektual dan Humanitas Puisi) - Siti Anshoriyah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
A poet, thinker, as well as unique personality af Abbasid Baghdad, Abu Nuwas has passed his time towards progressivekind of thought His works demonstrate a bombastic vulgar, and controversial expression of his humanity and intellectuality. Abu Nawas propased us an alternative view in seeing tauhid as liberating human from cultural restriction as reflected in the formality of sharia. Here is the place where progressive poems should be rightly placed